Stimulatory Effects of Low Intensity Laser Therapy on the Healing of Rabbit Tibial Defects - Nam, Nguyen Hoai; Sukon, Peerapol; Tangkawattana, Sirikachorn; Sutthiprapaporn, Pipop; Rattana-arpha, Pornpop; Kampa, Naruepon (The Thai Journal of Veterinary Medicine, 2014)
The present study was to investigate the effects of low intensity laser therapy (LILT) on the healing of rabbit tibial defects. Circular defects were perforated at the medial site of tibial crests on both hind legs of 18 male New Zealand White rabbits. The defects were randomly allocated into 3 groups (n=12): 1) defects irradiated with LILT, at 4 J/cm2 (LS4); 2) defects irradiated with LILT, at 20 J/cm2 (LS20), and 3) defects receiving sham treatment (control group). Irradiation began 24h after surgery, and repeated every 48 h, with a total of 8 sessions. In the 3rd and 6th weeks after surgery, the rabbits were euthanized, and the healing of defects was assessed by cone beam computed tomography, qualitative and quantitative histological techniques. Results showed that the 2 dosages of LILT similarly and significantly enhanced bone healing by increasing the bone area fraction in the 3rd week and the density of newly formed bone tissues in the 6th week after surgery. In conclusion, our findings support the hypothesis that LILT could improve the healing of the rabbit tibial defects via increased bone formation. The equal positive effects of the 2 settings suggest that the lower dosage of LILT may be more preferable and practical than the higher one in bio-stimulation of healing of bone fractures/defects.